Stroke after Initiating IV Penicillin for Neurosyphilis: A Possible Jarisch-Herxheimer Reaction - Vineet Punia; Appaji Rayi; Adithya Sivaraju (Case Reports in Neurological Medicine)
Introduction. Syphilis incidence has increased in the US in the last decade. Jarisch-Herxheimer reaction (JHR) is a well-documented adverse effect of penicillin treatment in syphilis. Stroke has not been reported as part of its phenomenology. Case Report. A 57-year-old man presented with worsening memory. His minimental status examination score was 14/30. Serum RPR test was positive and VDRL test in the CSF was reactive. Within six hours of first dose of IV crystalline penicillin G, he was found to have hemineglect and difficulty moving the left leg. MRI of the brain showed multiple acute ischemic strokes. Immediate MRA ruled out vascular occlusion. Penicillin treatment was stopped. Four hours later, he was found to be febrile and had two episodes of generalized tonic-clonic seizures. Conclusions. We report a case of confirmed neurosyphilis with no known modifiable stroke risk factors, who developed acute ischemic stroke and other constitutional symptoms consistent with JHR after IV penicillin. This is the first reported case in literature where an acute ischemic stroke can be attributed to Jarisch-Herxheimer reaction. Given an increase in incidence of syphilis in recent years, our case underlies the importance of keeping in mind potential catastrophic drug adverse reactions in neurosyphilis patients.